Failure Analysis at Stem Valve Fire Hydrant in LNG Plant - Mrihardjono, Juli; Pohan, Herman Abidin; Darmanto, Seno (Journal of Vocational Studies on Applied Research, 2019)
Hydrant is one of fire extinguisher fix system that use pressure water and flowed through the pipes and fire hose. There are more 250 Hydrant in this LNG Plant and based on finding at the field, many stem valve of outlet hydrant in fracture condition, therefore the author wants to analyze about the problem from this material, this reserch aims to find out root cause dan conduct failure analysis, method of reserch that conducted is visual check  to predict possible cause from failure of stem valve fire hydrant and then conducted fractographic analysis to find out what type of fracture that happen to this material and Tensile Strenght Test to Find out the the actual strenght of the material